Baby corn fermented vinegar and its vapour control postharvest decay in strawberries - Krusong, W.; Jindaprasert, A.; Laosinwattana, C.; Teerarak, M. (My University, 2015)
Infection by Botrytis cinerea is a major cause of postharvest decay in strawberries. The efficacy of baby corn fermented vinegar (BFV) for growth inhibition of B. cinerea was investigated by diffusing 0%-0.225% acetic acid from BFV or glacial acetic acid into potato dextrose agar. BFV containing 0.225% acetic acid completely inhibited the growth of B. cinerea. Strawberry-flavoured baby corn fermented vinegar (SF-BFV) was developed to mask unfavourable smells caused by BFV. The effectiveness of BFV liquid and vapour for controlling postharvest decay in strawberries was evaluated along with associated sensory analyses. Taste panellists readily accepted fruit that had been sprayed with SF-BFV or exposed to BFV vapour, both treatments that significantly reduced fruit decay. Strawberries inoculated with B. cinerea were also tested. Shelf life at 4°C of strawberries sprayed with SF-BFV was extended to 7 days while that of fruit exposed to BFV vapour was extended to 11 days.
Keywords: acetic acid vapour; baby corn fermented vinegar; Botrytis cinerea; shelf life; strawberry